Characteristics, management and production performance of ‘Nagal’ pig in tribal production system of North Eastern Hill region of India - Yadav , Dinesh Kumar; Singh , Mahak; Dige , Mahesh Shivanad; Zeliang , Hiabe (Journal of Livestock Biodiversity, 2025)
Nagal pigs are favored by tribal farmers due to their rapid growth rate, large litter size, black colour, and unique pork taste. This study, carried out in six districts of Nagaland, involved observations and interviews with pig owners, employing a pre-structured questionnaire to detail the morphology of ‘Nagal’ pigs, along with their management practices and production performance. Nagals are long, deep-bodied and black pigs. They have a short snout gently curved upward. Their top line is slightly concave. They have large, wide and drooping ears, partially obscuring their vision. Nagal pigs breed around the year. For males, the age at first mating is 6-7 months, while in females it is 7-8 months. The age at first farrowing is about 12 months with a farrowing interval of 5-6 months.The average litter size is sizeable, ranging from 7 to 20 piglets, although some sows may produce litters as large as 26.The gestation period is around 114 days. They are raised under intensive backyard management and fed on rice, corn, wheat bran, rice polish, plant leaves and leftover kitchen scraps. Short snout, black colour, low hair density and large ears are the preferred traits. The results of this study will aid in the development of breeding and conservation strategies for this significant swine genetic resource of Nagaland.